COVID-19 Vaccine donations: Blessings and curses for Africa - Brenda Z. Kubheka; Tshowa Kabala (International Society of Global Health, 2022)
Africans face double jeopardy on life expectancy due to poverty and constrained vaccine access. The COVID-19 pandemic caused the 2021 crude death rate in South Africa to rise from 8.7 deaths per 1000 people in 2020 to 11.6 deaths per 1000 people in 2021. Vaccination access is critical and depends on international solidarity and collaboration for sustainable programs. History points to the critical need for African countries to safeguard national sovereignty and prioritise donations with broader development objectives. Donor assistance should focus on assisting countries to rise and thrive beyond the pandemic challenges. Reducing benefactor dependency requires countries to be intentional about raising and securing financial resources to sustain vaccine access for the current and future generations. The assistance should focus on facilitating development, meaning investing in countries to thrive beyond the pandemic turbulence. For the sake of Africa's people and her future generations, current barriers to equitable vaccine access must be scrutinised. We do not know how many vaccine booster shots will be required in the future and the impact on Africa's health and socioeconomic standing. Global collaboration grounded on bolstering local manufacturing capacity is essential for Africa's sustainable access and distribution.